Analysis of the Efficacy of Acupuncture Combined with Rehabilitation Training in the Treatment of Upper Limb Spasm after Stroke: A Systematic Review and Meta-Analysis. (9th August 2022) - Liao, Yantan; Liu, Fengbin; Yang, Jingda; Ma, Qishou; Li, Junzhe; Chen, Yihui; Wu, Jiayong
Abstract : Objective . Systematic evaluation of the efficacy of acupuncture combined with cognitive rehabilitation training in the treatment of upper limb spasm after cerebral apoplexy. Methods . The data of CNKI, CBM, CQVIP, Wanfang, and the libraries of Pubmed and Cochrane were searched by computer, and the related literatures about acupuncture combined with cognitive rehabilitation training in the treatment of cognitive dysfunction after stroke were searched. The search time is from January 1, 1995 to January 1, 2022. All data segments were independently analyzed and extracted by two evaluators. After evaluating the quality of the methodology, meta-analysis was carried out by using the RevMan5.4 software. Results . Finally, 11 studies were included, with a total of 789 subjects. The results of meta-analysis indicated that acupuncture combined with cognitive rehabilitation training was superior to simple cognitive rehabilitation training or drugs in the following aspects, the difference exhibited statistically significant, the total effective rate (RR = 1.58, 95% CI), latency of P300 (MD = − 18.46, 95% CI), amplitude of P300 (MD = 1.23, 95% CI (0.82), P < 0.00001, 95% CI (0.31)), and activity of daily living (ADL), respectively, were significantly higher compared to the control group (P < 0.00001 ), and the difference was statistically significant (P < 0.05 ). Based on the results of systematic evaluation, the GRADE system recommendation classification method is used to evaluate the quality of evidence. The results show that the level of evidence is low and the intensity of recommendation is weak. Conclusion . The results of this meta-analysis suggest that the curative effect of acupuncture combined with cognitive rehabilitation training is better compared to simple cognitive rehabilitation training or drugs. However, due to the low quality of the original literature, it needs to be confirmed by multicenter, high-quality, large-sample randomized blind controlled trials in the future.